2019
DOI: 10.1186/s12914-019-0188-4
|View full text |Cite
|
Sign up to set email alerts
|

Sewing shirts with injured fingers and tears: exploring the experience of female garment workers health problems in Bangladesh

Abstract: BackgroundThe ready-made garment industry in Bangladesh not only contributes to the nation’s economic development, but has created income opportunities for women, benefiting their whole family. However, these benefits come at considerable cost to the women. This research examines how the work environment and gendered family role in this conservative society affect the health of the female industrial workers.MethodsA qualitative study employed in-depth interviews (n-20) and focus group discussions with female g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
4
14
1
1
Order By: Relevance
“…Sex is signi cantly associated with most of the diseases registered in this study; female workers were diagnosed with more diseases compared to the males. A qualitative in-depth interviewing and focus group discussion with 24 female workers from Bangladesh indicated that female workers suffered from several types of diseases in the garment factories (32). The morbidity assessment study by Singh and colleagues (16) also revealed that female workers in the textile had more severe anemia than the males which is similar to the nding of the present study, and this might be related to the monthly menstrual cycle among females.…”
Section: Personal Factorssupporting
confidence: 84%
“…Sex is signi cantly associated with most of the diseases registered in this study; female workers were diagnosed with more diseases compared to the males. A qualitative in-depth interviewing and focus group discussion with 24 female workers from Bangladesh indicated that female workers suffered from several types of diseases in the garment factories (32). The morbidity assessment study by Singh and colleagues (16) also revealed that female workers in the textile had more severe anemia than the males which is similar to the nding of the present study, and this might be related to the monthly menstrual cycle among females.…”
Section: Personal Factorssupporting
confidence: 84%
“…High work-related demands and poor interpersonal resources represented key components of work stress and were important determinants of poor health. A qualitative study employed in-depth interviews ( n -20) and focus group discussions with female garment workers ( n -4) in two cities of Dhaka district (Akhter, Rutherford, & Chu, 2019) and explored the female garment workers’ health problems such as joint pain, continuous headache, eye pain and difficulty in breathing associated with inhaling fabric. The researchers have observed that inadequate lighting, constantly sitting in one position without back rest and continuous noise from hundreds of machines make them feel permanently tired.…”
Section: Resultsmentioning
confidence: 99%
“…Fast fashion retailers depend on low-wage workers in underdeveloped countries to keep costs down, make clothes in less time, and meet the lead time. These employees are not only not paid adequate living wages, but also labor under poor working conditions, are exposed to hazardous chemicals and the health risks associated with repetitive motion tasks, and even suffer abuse from managers [44,45]. Even though most of these workers are not employed directly by fast fashion retailers, these global companies are not free from increasing criticism of the ethical and social problems associated with sweatshops in developing countries.…”
Section: Dark Sides Of Fast Fashionmentioning
confidence: 99%